2020
DOI: 10.18196/ijief.3238
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Zakat Integration as Source of State Revenue

Abstract: In the era of new public financial management, where society participation and cost sharing in public goods provision are inevitably pursued by government, some sources can still be explored such as zakat, infaq, and sadaqah as social awareness activities for Muslims that are prevalent in the community. There are also other donations on the basis of certain motivations which can reduce the burden of tax revenue to support public policy. The phenomenon of mutual cooperation and caring to help others through soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
0
9
0
3
Order By: Relevance
“…However, there remain some challenges and structural barriers to integrating Zakat in the fiscal framework. Yasni and Erlanda (2020) revealed that incorporating Zakat as an alternative state revenue source can be challenged by regulatory oversight, building public trust, enhancing compliance, harmonizing rules with other religious communities and ensuring spending flexibility. A key challenge in this case involves levying both Zakat and tax on the same group of individuals and industries.…”
Section: Potential Of Zakat In Fiscal Frameworkmentioning
confidence: 99%
“…However, there remain some challenges and structural barriers to integrating Zakat in the fiscal framework. Yasni and Erlanda (2020) revealed that incorporating Zakat as an alternative state revenue source can be challenged by regulatory oversight, building public trust, enhancing compliance, harmonizing rules with other religious communities and ensuring spending flexibility. A key challenge in this case involves levying both Zakat and tax on the same group of individuals and industries.…”
Section: Potential Of Zakat In Fiscal Frameworkmentioning
confidence: 99%
“…Modal sosial atau social capital yang terbentuk mempengaruhi keberhasilan pengumpulan dana untuk pembangunan infrastruktur menggunakan crowdfunding (Arifin & Wisudanto, 2017). Penelitian lain menunjukkan bahwa terdapat berbagai rintangan yang timbul ketika pemerintah ingin menggunakan zakat yang merupakan dana dari umat beragama sebagai sumber pendapatan negara (Yasni & Erlanda, 2020).…”
Section: Pendahuluanunclassified
“…Selain itu juga terdapat hasil penelitian yang menyampaikan bahwa dana pembangunan dapat dikumpulkan menggunakan skema crowdfunding dengan tetap memperhatikan ketentuan syariat dengan skema tabarru' atau tijaroh (Pratama et al, 2020). Sementara satu penelitian lainnya menyatakan bahwa pemerintah harus mencari sumber alternatif pendapatan selain yang telah digunakan dalam mekanisme APBN, dan gagasan yang disampaikan adalah pengintegrasian zakat sebagai sumber pendapatan negara karena pendapatan pajak yang mengalami fluktuasi serta tingkat kemiskinan di negara Indonesia yang cenderung tinggi (Yasni & Erlanda, 2020).…”
Section: Penelitian Terdahuluunclassified
“…Para ulama harus membuka wawasan menyangkut potensi zakat dimaksud serta mendukung Baitul Mal sebagai lembaga yang mandiri dan profesional dalam mengelola zakat, yang merupakan salah satu sumber pendapatan yang sangat potensial untuk menjadi alternatif bagi pemberdayaan ekonomi rakyat. 19 Hasil penelitian menunjukkan bahwa kontribusi zakat terhadap sumber pendapatan asli daerah lainnya masih relatif kecil karena selama ini disalurkan kepada program pendidikan, kesehatan, sosial keagamaan dan modal usaha. Di samping itu zakat merupakan ibadah sosial yang memerlukan keterlibatan negara dalam mengurusnya.…”
Section: Hasil Dan Pembahasan Implementasi Pengelolaan Zakat Sebagai Pad Oleh Baitul Mal Acehunclassified